Burgers, coffee or bureks? A bottom-up perspective on everyday identity consumption, nationalism, and geographies of belonging in contemporary Serbia - Laurent Tournois (Acta Politologica)
The last days of the Yugoslav Federation and the nationalist decade that followed brought to the fore negative categorizations and ‘ancient’ geographies of belonging. Since 2012, the ruling elite have sought to contain nationalism and to rebuild the image of a modern nation using consumption as a political tool by bridging (again) East and West. This contention is grounded in two entangled theoretical perspectives on consumption and national identity building. Adopting a historical narrative scheme, the original material collected in this study from 45 semi-structured customer and problem-centered expert interviews and extensive ethnographic fieldwork contributes to contextualizing and problematizing consumption routines towards McDonald’s restaurants, Simit Sarayi, and Starbucks coffee shops. This paper highlights that, daily, individuals have developed their own interpretative space within which to operate, exhibit their identity, and express to whom their affinity goes, leading to cultural paradoxes in certain situations.